Analysis of the status of providing specialized medical and preventive care to nephrological patients in Ukraine in 2020 - M.O. Kolesnyk; N.I. Kozlyuk; O.O. Razvazhaeva (Український Журнал Нефрології та Діалізу, 2021)
Objective: rating evaluation of specialized medical and preventive care for renal patients in different regions of Ukraine and Kyiv in 2020 using the method of complex statistical coefficients.